“Participation”, “negotiated settlement” of conflicts and (neo) extractivism in Brazil: The Serra do Gandarela National Park (Minas Gerais, Brazil) - Orduz-Rojas, Claudia Marcela; Barros-Pereira, Doralice Barros-Pereira; Bruno-Dias, Janise (Revista de Estudios Andaluces, 2018)
The adoption of mechanisms of participation and techniques for management and negotiated settlement of conflicts have become crucial in order to solve environmental “issues” (Monteiro et al., 2012; Mungai, M., 2008). Based on the struggles with Vale S.A. and the creation of the Serra do Gandarela National Park (PNSG), situated in the metropolitan area of Belo Horizonte, Minas Gerais (Brazil), we have studied the limits of the consensus paradigm in the standpoint of (neo) extractivism, taking into account the typology of participation by Pimbert, M. & Pretty, J. (1995). The work has been elaborated from official documentation, semi-structured interviews and the observation of events of participation and negotiations as Public Hearings, Public Consultations, Work Groups and Direct Negotiation Roundtables. We conclude that the adoption of such participatory and consensual mechanisms produces a delusion related to "participation" and "harmonization" of different interests. In addition, the settlements made along extensive negotiation processes proved to be inadequate and deliberately neglected, once again granting the mining companies with access and territorial control and the reproduction of its production space.